The mythological representation in the new artistic strategies - Ramos Fabra, Lidón; Pesqueira Calvo, Carlos (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The role of augmented reality, virtual reality or algorithms in society is increasing. It is enough to check the amount of technology that is being integrated as a habitual element in everyday life. The objective of our study is based on combining both the usefulness and aesthetic possibilities offered by augmented reality offers with the study of mythology and its dissemination. In the present work we focus specifically on the mythology about the founding of Madrid. The aim is to establish to what extent it is possible to represent the spirit of myth through new technologies.